Espacio urbano e imágenes acuáticas en "Materia dispuesta" de Juan Villoro - Di Biase Castro, Elisa T. (El Colegio de México, 2017)
Reception: July 15, 2015Accepted: October 11, 2016.Material images —in the sense that Gaston Bachelard understands them— play an important role in the imagery dimension that space acquires in Mexico City; that is to say, the way the four elements are configured serves to a great extent to shape the identity of this hipermetropolis. Juan Villoro, one of the contemporary writers most closely linked to the Mexican capital, is very sensitive to this material dimension. His novel Materia dispuesta interprets the material aspect of the city in terms of a Bildungsroman. The main character and the city undergo a synchronic evolution: their meanings and their bodies intertwine. This study addresses the aquatic imagery in the novel.